Effects of pH, Temperature, Dissolved Oxygen, and Flow Rate on Phosphorus Release Processes at the Sediment and Water Interface in Storm Sewer - Haiyan Li; Liang Liu; Mingyi Li; Xiaoran Zhang (Journal of Analytical Methods in Chemistry)
The effects of pH, temperature, dissolved oxygen (DO), and flow rate on the phosphorus (P) release processes at the sediment and water interface in rainwater pipes were investigated. The sampling was conducted in a residential storm sewer of North Li Shi Road in Xi Cheng District of Beijing on August 3, 2011. The release rate of P increased with the increase of pH from 8 to 10. High temperature is favorable for the release of P. The concentration of total phosphorus (TP) in the overlying water increased as the concentration of DO decreased. With the increase of flow rate from 0.7 m s−1 to 1.1 m s−1, the concentration of TP in the overlying water increased and then tends to be stable. Among all the factors examined in the present study, the flow rate is the primary influence factor on P release. The cumulative amount of P release increased with the process of pipeline runoff in the rainfall events with high intensities and shorter durations. Feasible measures such as best management practices and low-impact development can be conducted to control the P release on urban sediments by slowing down the flow rate.